AI를 활용한 PBL 기반 블렌디드 수업이 영어학습에 미치는 영향 - 윤광진; 맹은경 (현대영어교육, 2021)
The purpose of this study is to investigate the effect of PBL based blended instruction utilizing AI platforms on L2 learning. For this purpose, PBL based online and offline instruction utilizing various AI tools was implemented for one semester with 33 middle school students. Data were collected via English achievement tests and surveys on students’ affective factors and satisfaction on this instruction and t-test, ANOVA and Post-Hoc test were used to analyze the data. The results of this study were as follows. First, PBL based blended instruction utilizing AI platforms enhanced students’ overall English achievement. Especially students’ speaking and writing skills were improved significantly. Second, this instruction improved students’ affective factors significantly: interest, participation, motivation, and confidence. Third, students showed a high level of satisfaction toward this PBL based blended instruction overall. Findings and pedagogical and research implications are discussed.
Keywords: AI platform; PBL; blended instruction; L2 learning; AI플랫폼; 문제기반학습; 블렌디드 수업; 제2언어 영어학습